Towards UHI mitigation adopting park cooling effect: Two- decade literature review for a theoretical framework - Haldar, Sudeshna; Dey, Priyanka (Mitigation and adaptation strategies for global change, 2024)
The unexpected population increase in megacities has caused the urban heat island (UHI) effect. The Park Cooling Intensity (PCI) effect offers natural cooling from urban parks that can balance UHI. Doubling the urban population in the next two decades is expected to cause a rise in high-rise buildings. This research thoroughly evaluates the knowledge accumulated by adopting a Systematic Literature Review (SLR) since 2000 regarding the relationship between UHIs and PCI. To identify experimental trends, methodological trends, geographical interdependence, and research gaps in UHI mitigation, results obtained from 9 nations and 11 Köppen-Geiger climate zones are examined and compared from 55 selected research papers. Five significant topics are used to guide a thorough content analysis. The first section of the manuscript enlists identified factors of UHI mitigation affecting urban heat. The second section presents an observation table about how the different researchers have amalgamated the above-discussed factors to infer the comparison among the discussed literature. The study has identified three prominent research gaps explaining limitations in research: 1) current research trends, 2) governing factors of socio-economic and environmental aspects, and 3) exploration of evapotranspiration rates in terms of Bowen ratio. This review will aid researchers in selecting coping mechanisms for urban climates of extreme heat.